Assessing ion-exchange properties and purity of lipophilic electrolytes by potentiometry and spectrophotometry - Silvester, Debbie; Grygolowicz-Pawlak, Ewa; Bakker, Eric (Elsevier, 2010)
Many ionic salts synthesized using metathesis are often found to contain significant amounts of impurities, despite careful control of the weighing of starting materials. In this work, a potentiometric method is devised to monitor ion-exchange properties (or 'purity') of an organic solvent containing a lipophilic electrolyte. Its permselective behaviour is monitored by treating the solvent as a liquid membrane and contacting it with two aqueous solutions with different electrolyte activities. This electrolyte mismatch results in a drastic potential change when excess lipophilic cation-exchanger is titrated with anionexchanger, altering the membrane from being cation to anion responsive. Here, the cation-exchanger potassium tetrakis(4-chlorophenyl)borate (KTpClPB) dissolved in nitrobenzene was titrated with tetradodecylammonium chloride (TDDACl), in contact with Ag/AgCl electrodes placed in aqueous 1 M and 102 M KCl, respectively. The predicted potential change of 214 mV was observed at the equivalence point, forming the inert lipophilic electrolyte ETH 500, in a very small concentration range of added anion-exchanger (0.8% for 10 mV), suggesting good precision. The approach was confirmed by monitoring absorbance and fluorescence intensity changes of the chromoionophore Nile Blue. This method may be applied for the synthesis of a range of highly lipophilic salts for which established metathesis protocolsare not suitable.